Vitamin D insufficiency and its contributing factors in primary school-aged children in Indonesia, a sun-rich country - Aman Pulungan; Frida Soesanti; Bambang Tridjaja; Jose Batubara (Korean Society of Pediatric Endocrinology, 2021)
Purpose The prevalence of rickets is increasing worldwide in association with an increase in vitamin D deficiency. This study aimed to investigate the vitamin D profile of healthy school-aged children in a sun-rich country and its contributing factors. Methods This cross-sectional study was conducted in 120 healthy children from 7-12 years of age who live in Jakarta, Indonesia. Their demographic status, sun exposure duration time, and lifestyle were recorded using a structured questionnaire. Serum calcium, phosphate, bone-alkaline phosphatase (B-ALP), and 25-hydroxy vitamin D (25(OH)2D3) levels were measured. The participants were categorized into vitamin D sufficient and non-vitamin D sufficient groups, and we analyzed variables that contributed to the 25(OH)2D3 level. Results Of the participants, 73 (60.8%) were vitamin D sufficient, 45 (37.5%) were vitamin D insufficient, and 2 (1.7%) were vitamin D deficient. Sex, age, body mass index, Fitzpatrick skin type, daily milk intake, and clothing type were not different between the vitamin D sufficient and non-vitamin D sufficient groups. There were no differences in serum calcium, phosphate, and B-ALP between the 2 groups. Sun exposure time was significantly longer in the vitamin D sufficient group compared with that in the non-vitamin D sufficient group (511.4 min/wk vs. 318.7 min/wk, P=0.004), and this effect remained consistent on multivariate analysis after adjustment for covariates (adjusted odds ratio, 1.002; 95% confidence interval, 1.000-1.003). More participants in the vitamin D sufficient group did not use sunscreen (59 vs. 27, P=0.02), but this finding was inconsistent with our multivariate analysis. Conclusions Despite year-round sun exposure, approximately 1 in 3 primary school-aged children had insufficient vitamin D level. Sun exposure duration was a major contributing factor.